Health care leaders’ perspectives on the business impact of mobile health clinics - Mollie M. Williams; Sarah T. Bui; Josephina S. Lin; Gregory H. Fan; Nancy E. Oriol (International Journal for Equity in Health, 2023)
Abstract Background By analyzing how health care leaders in the United States view mobile health programs and their impact on the organization’s bottom line, this study equips those who currently operate or plan to deploy mobile clinics with a business case framework. Our aim is to understand health care leaders’ perspectives about business-related incentives and disincentives for mobile healthcare. Methods We conducted 25 semi-structured key informant interviews with U.S. health care leaders to explore their views and experiences related to mobile health care. We used deductive and inductive thematic analysis to identify patterns in the data. An advisory group with expertise in mobile health, health management, and health care finance informed data collection and analysis. Results In addition to improving health outcomes, mobile clinics can bolster business objectives of health care organizations including those related to budget, business strategy, organizational culture, and health equity. We created a conceptual framework that demonstrates how these factors, supported by community engagement and data, come together to form a business case for mobile health care. Discussion Our study demonstrates that mobile clinics can contribute to health care organizations’ business goals by aligning with broader organizational strategies. The conceptual model provides a guide for aligning mobile clinics’ work with business priorities of organizations and funders. Conclusions By understanding how health care leaders reconcile the business pressures they face with opportunities to advance health equity using mobile clinics, we can better support the strategic and sustainable expansion of the mobile health sector.